Synthesis of functionalized cationic glycolipids for targeted drug delivery / Goh Ean Wai - Goh , Ean Wai (2019)
Amphiphilic glycolipids are known for their role in cellular recognition processes. This has created interest in using their assemblies, particularly vesicles, as drug carriers, because their strong intermolecular hydrogen bonding ensures high stability. Introduction of biological recognition domains onto the vesicular surface enables a targeting delivery of drugs to specific cells. This prevents unwanted interaction between the drug and non-target cells, thus minimizing drug’s side effects. A series of functionalized glycolipids carrying CLICK functionality was prepared, which renders a bioconjugation opportunity with suitable antigens or targeting ligands under mild conditions. To ensure coupling efficiency, an ethylene oxide spacer was introduced between the CLICK functionality and the sugar head group to provide flexibility to the anchor. The incorporation of a quaternary ammonium cation, based on the Menshutkin reaction, gave rise to cationic character of the glycolipids. The electrostatic repulsion between these cations increased the hydrophilic surface area, thereby leading to an increased curvature in the assemblies and resulting in the formation of micellar aggregates in water instead of vesicles. All glycolipids exhibited very similar assembly behaviour, despite differing in the position of the functionalized linker on the sugar head group. Application of the compounds as co-surfactant for vesicle preparation furnished uniformly small-sized and stable vesicles, as indicated by their zeta potential.